PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN KUIS INTERAKTIF UNTUK MENINGKATKAN MINAT BELAJAR BAHASA INDONESIA SISWA KELAS V SDN PARANG TAMBUNG 1 MAKASSAR - Sefriana Sefriana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to determine the application of the Problem Based Learning (PBL) learning model using interactive quizzes to increase the learning interest of fifth grade students of SDN Parang Tambung 1 Makassar in the odd semester of the 2024/2025 school year. This research is a class action research (PTK) which was carried out in 2 cycles. The data analysis technique used in this research is qualitative and quantitative data analysis using observation sheets and tests. The results showed the Problem Based Learning (PBL) learning model to increase the learning interest of fifth grade students of SDN Parang Tambung 1 Makassar. Based on the data obtained in cycle I, it can be seen from the increase in student interest in learning from cycle I to cycle II. In cycle I, the percentage of students' interest in learning was 74.25%. Furthermore, in cycle II, the percentage of students' interest in learning increased to 89.78%. Based on the analysis and discussion, it is concluded that the application of the Porbelm Based Learning model can effectively improve students' Indonesian learning outcomes.